Blockchain Interfaced Sacure E-Voting System - Shrestha, Raj; Sah, Rajiv; Shrestha, Sabin; Sarawagi, Shailja; Adhikari, Nanda Bikram (Journal of the Institute of Engineering, 2020)
National elections are a big deal which has a major role in the development and progress of a country. The security of an election is in fact the matter of national security. Current voting systems in the context of Nepal and other parts of the world are still traditional and insecure. From the dawn of democracy, elections are still based on pen and papers. While there are new electronic voting machines, these systems have a high risk of rigging and are prone to failure, crashes, and attacks from intruders. The stated problems can be addressed through the implementation of new technology namely Blockchain for a transparent and reliable voting process. A blockchain based voting platform has been built to make the voting process digital, secure, reliable and intuitive. The votes casted by voters are stored in the blockchain, thus making it immutable and secure. The system can be scaled based on the requirements of an election. Voters can login to the system with the help of encrypted identification. This encrypted identification will lead to secure voting process. A separate portal for both voters and the election commission reduces the election hassle and time. So, in this system, it is demonstrated how the use of blockchain platform could contribute to modern elections using Ethereum, smart contracts and distributed systems to provide voters with secure, transparent and reliable voting platform.